Analytical modeling on collapse resistance of steel beam-concrete slab composite substructures subjected to side column loss. (15th August 2018) - Li, Guo-Qiang; Zhang, Jing-Zhou; Jiang, Jian
Highlights: An analytical method is proposed to predict the resistance of composite beam-slab substructures due to side column loss. Parametric studies are conducted to investigate the effect of various structural parameters on load–displacement curves. The contributions of concrete slab and steel beams to the collapse resistance are quantitatively identified. Abstract: This paper proposes an energy-based method to determine the structural responses of steel beam-concrete slab composite substructures under side column removal scenarios. A tri-linear resistance-displacement curve is proposed. Three factors contributing to the internal energy dissipation are accounted for, including the extension of reinforcing bars and steel beams, the additional bending moment induced from membrane forces in the slab and tensile forces in beams, and sectional bending moment along yield lines of the slab. Parametric studies are conducted based on validated finite element models to investigate the effect of slab planar aspect ratio, slab thickness, slab reinforcement ratio and beam section height on the behavior of composite beam-slab substructures subjected to side column loss. The numerical results show that these four parameters have limited effects on the yield displacement of the substructure. The accuracy and effectiveness of the proposed method are verified against numerical results with errors less than 15%. It is found that the first two factors considerably contributed to the collapse resistance of the substructures at large deflections, by accounting for more than 70% of the total energy dissipation capacity. The contribution from the slab at the collapse limit state is mainly influenced by its reinforcement ratio.